2004
DOI: 10.1111/j.0013-9580.2004.04504.x
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone Analogs That Positively Modulate GABAA Receptors Protect against Partial Seizures Induced by 6‐Hz Electrical Stimulation in Mice

Abstract: Summary:Purpose: Low-frequency (6 Hz), long-duration (3 s) electrical stimulation in mice produces seizures characterized by immobility, focal clonus, and automatic behaviors reminiscent of human limbic epilepsy. Renewed interest has been expressed in this seizure model with the recognition that it is sensitive to a broad spectrum of anticonvulsants (AEDs) and may have distinct pharmacologic responsiveness from other in vivo tests of AED efficacy. Here we sought to determine whether the progesteronederived neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 6 publications
6
154
0
Order By: Relevance
“…The lack of activity in mice raises doubt that effects on GABA mechanisms contribute in a substantial way to the seizure protection conferred by the diet. Recently, we found that the ketogenic diet is highly protective against 6 Hz electroshock seizures in mice, a model of limbic seizures that shows a similar sensitivity to anticonvulsant agents that act on GABA systems as does the pentylenetetrazol test [32,33] (A.L.H., M. Lyle, M.G., and M.A.R., unpublished data). In particular, anticonvulsant agents that target GABA systems are highly effective and relatively potent in the 6 Hz model.…”
Section: Gaba Systemsmentioning
confidence: 89%
See 1 more Smart Citation
“…The lack of activity in mice raises doubt that effects on GABA mechanisms contribute in a substantial way to the seizure protection conferred by the diet. Recently, we found that the ketogenic diet is highly protective against 6 Hz electroshock seizures in mice, a model of limbic seizures that shows a similar sensitivity to anticonvulsant agents that act on GABA systems as does the pentylenetetrazol test [32,33] (A.L.H., M. Lyle, M.G., and M.A.R., unpublished data). In particular, anticonvulsant agents that target GABA systems are highly effective and relatively potent in the 6 Hz model.…”
Section: Gaba Systemsmentioning
confidence: 89%
“…Reduced availability of oxaloacetate along with robust availability of α-ketoglutarate from high activity of the first part of the Krebs cycle leads to low aspartate levels. It has been hypothesized that more glutamate is thus accessible to glutamic acid decarboxylase for production of GABA [33]. Not all Krebs cycle intermediates are shown in the schematic.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3α-androstanediol at normal ED 50 dosage does not protect seizures induced by gluatamate receptor agonists such as kainic acid, NMDA and 4-aminopyridine (Reddy, 2004b). 3α-Androstanediol is structurally similar to allopregnanolone and conferred seizure protection in the 6-Hz electroshock model of epilepsy (Kaminski et al, 2004). Overall, the anticonvulsant profile of 3α-androstanediol is highly consistent with other GABA A receptor modulating neurosteroids including allopregnanolone and THDOC, which have similar spectrum of anticonvulsant activity in animal seizure models (Belelli et al, 1989;Kokate et al, 1994;Reddy and Rogawski, 2002;Reddy et al, 2004;Reddy, 2006).…”
Section: Anticonvulsant Activity Of 3α-androstanediolmentioning
confidence: 97%
“…5 GNX prevented clonic and behavioral seizures caused by low-frequency (6 HZ) long-duration (3 s) electrical stimulation in mice. 6 PTZ-induced seizures in rats did not develop tolerance to chronic treatment with GNX. 7 …”
Section: Chemistry and Formulationmentioning
confidence: 85%